Clinical and prognostic significance of matrix metalloproteinases in patients with myocardial infarction - T. B. Pecherina; O. L. Barbarash (Фундаментальная и клиническая медицина)
Biomarkers are often used as a surrogate measure in the assessment of risk, severity, and prognosis of the disease. For the optimal use of biomarkers in predicting cardiovascular risk, they should demonstrate reproducibility in sequential quantitative measurements and show high sensitivity and specificity. In recent years, classic biomarkers of myocardial necrosis such as troponins were complemented by inflammatory markers (C-reactive protein, cytokines, matrix metalloproteinases) and markers of myocardial dysfunction (atrial and cerebral natriuretic peptides). Currently, conventional biomarkers are widely used for the timely diagnosis of myocardial infarction while an increasing number of novel markers are utilized to evaluate the risk of adverse outcomes in patients with acute coronary syndrome.